Precursors of the treatment failure of mycobacteriosis in patients with HIV - M. A. Savchenko (Журнал инфектологии)
Purpose. Analyze the dynamics of clinical and laboratory parameters, the outcomes of the disease on various treatment regimens. To identify the main markers of unfavorable outcome or protracted course of the disease.Materials and methods. The study included 70 patients with HIV and mycobacteriosis who received complex therapy (antiretroviral and specific antibacterial drugs). Depending on the outcome of the disease, two groups were distinguished: clinical cure (n = 38) and lethal outcome (n = 32). The clinical manifestations of pathology, laboratory indicators at different stages of treatment, the scheme and terms of the therapy being carried out were analyzed on the basis of data from medical histories and ambulatory patient records.A statistical analysis was performed, the efficacy of therapy was evaluated using the Kaplan-Meier method, the macrolide in the first line of antibacterial therapy used was taken as the basis.Results. All patients who died developed a disseminated form of the process. In cases when MAI developed within the unmasking immune restoration syndrome patients were prognostically more favorable (p <0,05). In the clinical cure group, a significantly higher level of CD4 lymphocytes was recorded before treatment (33,3 ± 7,1 versus 9,9 ± 3,2 cells / μl, p <0,05). A significant difference in the level of CD4 persisted after a month of complex therapy (79,0 ± 13,4 versus 32,2 ± 9,1, p <0.05). In addition to higher immunity values, the first group also had a higher hemoglobin level after a month of treatment (108,3 ± 3,2 g / l versus 76,7 ± 5,2 g / l, p <0,05). The regression of intoxication and fever was observed earlier in the cure group. When studying the used macrolide basis for the treatment of mycobacteriosis, it was found that survival term was significantly higher among patients who received clarithromycin in the first line (Kaplan – Meier, p <0,05 Breslow, Tarone-Ware). According to this sample, the introduction of aminoglycoside to the treatment regimen did not make significant changes in the timing and prognosis of treatment.Conclusion. Prolonged persistence of the symptoms of the disease, persisting deep immunodeficiency and anemia of moderate or severe degree are associated with an unfavorable outcome. According to this sample, clarithromycin should be considered the drug of choice for the treatment of mycobacteriosis in HIV.